HLA-B*39:06 strong association with autoimmune diabetes. (October 2022) - Liu, Shan; Wen, Yurong; Liu, Yunke; Abualrous, Esam; Ouyang, Zhenlin; Spappen, Robbert; Garstka, Malgorzata A.
Abstract : In type 1 diabetes mellitus (T1DM) insulin-producing pancreatic cells are destroyed by auto-reactive T cells. MHC class I molecules have only recently been recognized as an independent risk factor for T1DM. HLA-B*39:06 is the most predisposing MHC class I allele, independently of the long-known MHC class II haplotypes; however, the underlying mechanisms remain unknown. We determined the crystal structures of T1DM-predisposing B*39:06 and closely-related T1DM-protective B*38:01 subtypes complexed with the same peptide. We expressed and characterized both subtypes in cell lines. In both subtypes, the peptide bound in a conformation almost identical at the N and C termini, emphasizing the importance of the primary anchors for complex stability. However, binding of the secondary anchor differed, as well as the conformation of the exposed residues that are potential T cell receptor contact sites, with B*39:06 binding peptide in a more closed structure. Both alleles show similar cell surface expression. In addition, B*39:06, but not B*38:01 localized in the late endosomes. Endosomal localization was reduced when cells were cultured at 25oC, suggesting that B*39:06 remained at the cell surface, and indicating it may present sup-optimal peptides. Our data show that T1DM-predisposing MHC I allele binds peptide more strongly than the T1DM-protective allele, suggesting that B*39:06 may be more permissive in peptide selection and bind sub-optimal peptides. Such suboptimal peptides presented locally at the higher dose may contribute to auto-reactivity of CD8+ T cells. Ongoing experiments with Tapasin knock out cell line will further substantiate to the knowledge of B*39:06 strong association to T1DM.